Introduction. Between Health and Illness. Literary conceptualizations of physical and mental suffering in contemporary Nordic literature - Cymbrykiewicz, Joanna; Zańko, Aldona (Folia Scandinavica Posnaniensia, 2024)
The present text serves as an introduction to the special issue of Folia Scandinavica Posnaniensia, “Between Health and Illness,” which is devoted to contemporary discourse on health and illness in Nordic literatures. Even though Scandinavian countries rank highest in happiness and well-being, illness as a literary motif maintains constant popularity and interest among both writers and scholars. The editors provide brief presentations of each contribution, some of which originate from conference speeches held in December 2022 in Poznań.